Semiologi MS Glow for Men: Analisis Iklan Marshel Widianto dan Babe Cabita di Instagram: Analisis Semiologi Iklan MS Glow for Men oleh Marshel Widianto dan Babe Cabita di Instagram - Adella Eka Ridwanti; Poppy Febriana (Academia Open, 2024)
This qualitative descriptive study employs Roland Barthes' semiotic analysis to explore and elucidate the representation of glowing skin in the MS Glow For Men advertisement featuring Marshel Widianto and Babe Cabita. The research aims to depict how the portrayal of glowing skin is constructed in the advertisement and its impact. The findings reveal a depiction of a man with radiant, fresh, and brighter skin without altering its natural color. The scenes suggest that using MS Glow For Men enhances confidence and happiness, enabling men to appear more handsome irrespective of body type or skin tone. This advertisement challenges prevailing societal myths by featuring men with diverse characteristics, debunking the notion that skincare ads exclusively showcase individuals with fair skin, ideal body types, and conventional hairstyles. The implications of this study underscore the transformative potential of inclusive representations in beauty advertisements. Highlights : Semiotic Exploration: Unraveling the layers of meaning in the MS Glow For Men advertisement through Roland Barthes' semiotic analysis. Inclusive Representation: Breaking stereotypes by featuring Marshel Widianto and Babe Cabita, showcasing diversity in skin tones, body types, and hairstyles. Transformative Impact: Revealing the advertisement's potential to enhance confidence and challenge societal norms, emphasizing the power of inclusive beauty representations. Keywords: Glowing skin, Semiotic analysis, Beauty advertisements, Inclusivity, Marshel Widianto